Prevalence and patholoygy of Polioencephalomalacia in Goats - Divakaran Nair N (Centre of Excellence in Pathology, College of Veterinary and Animal Sciences, 1999)
Polioencephalomalacia (PEM) is a significant emerging diseases problem in goats. Although, PEM in goats was recognized and reported as early as 1956, its etiology is poorly understood and symptomatology, pathological features and therapeutic approach have not been well defined and documented.